Risk Factors and Protective Factors for Musculoskeletal Disorder (MSD) Complaints Among Office Workers: A Qualitative Study - Suraya, Anna; Situmorang, Susi Kesuma Pratiwi (Direktorat Penelitian, Pengabdian Masyarakat, Dan Kerjasama Universitas Binawan (DPPMK Universitas Binawan), 2025)
Musculoskeletal Disorders (MSDs) are a significant occupational health concern among office workers globally. Prolonged sitting, non-ergonomic postures, and static work positions associated with computer-based tasks contribute to physical discomfort and functional limitations. In Indonesia, MSDs remain underreported, and qualitative insights into workers' lived experiences are limited. This study aimed to explore the experiences, perceived causes, risk factors, and coping strategies related to musculoskeletal complaints among office workers in Jakarta, Indonesia. A qualitative study with a descriptive phenomenological approach was conducted from February to May 2024. Six office workers from a major insurance company who had worked for over three years participated in semi-structured interviews and field observations. Data were analyzed using Colaizzi’s seven-step method to identify emerging themes and validate participant experiences. Five key themes emerged: (1) experiences of MSD-related complaints, (2) work-related risk factors, (3) additional contributing factors, (4) strategies for symptom relief, and (5) factors that worsen symptoms. Participants commonly reported back pain and stiffness linked to prolonged sitting, poor posture, and mismatched office furniture. Other contributing factors included high body mass index (BMI), emotional fatigue, long working hours, and commuting conditions. Strategies such as regular exercise, stretching, hydration, and the use of pain relief patches were perceived to alleviate symptoms. Psychosocial stressors, including workload and interpersonal conflict, were found to exacerbate physical complaints. MSDs among office workers are influenced by a complex interplay of physical, psychosocial, and behavioral factors. Comprehensive workplace interventions addressing both ergonomic and psychosocial aspects are needed to mitigate MSD risks and improve worker well-being.